Has sclerostin a true endocrine metabolic action complementary to osteocalcin in older men?. Issue 7 (July 2016) - Confavreux, C.; Casey, R.; Varennes, A.; Goudable, J.; Chapurlat, R.; Szulc, P.
Abstract Summary The reported association between sclerostin and diabetes mellitus or abdominal fat may be biased by body size and bone mass. In older men, the association between serum sclerostin levels and metabolic syndrome lost significance after adjustment for bone mass. The association between sclerostin and energy metabolism needs further clarification. Introduction Sclerostin is associated with abdominal fat, but this relationship may be biased since both are associated with body size and bone mass. Osteocalcin is a bone-derived hormone regulating energy metabolism. We assessed the association between serum sclerostin and metabolic syndrome (MetS) accounting for whole body mineral content (BMC) and osteocalcin. Methods We studied 694 men aged 51–85 who had serum osteocalcin and sclerostin measurements. Results Sclerostin was higher in 216 men with MetS compared with those without MetS (p  < 0.005). Average sclerostin level increased significantly across the increasing number of MetS components. In multivariable models, higher sclerostin was associated with higher odds of MetS (odds ratio (OR) = 1.24/1 standard deviation (SD) increase [95 % confidence interval (95 % CI), 1.01–1.51];p  < 0.05). After further adjustment for BMC, the association of MetS with sclerostin lost significance, whereas that with osteocalcin remained significant. Men who were simultaneously in the highest sclerostin quartile and the lowest osteocalcin quartile had higher odds of MetS (OR = 2.14 [95 % CI, 1.15–4.18];p  < 0.05) vs. men being in the three lower sclerostin quartiles and three upper osteocalcin quartiles. After adjustment for whole body BMC, the association lost significance. Conclusions Higher sclerostin level is associated with MetS severity; however, this association may be related to higher whole body BMC. The adjustment for BMC had no impact on the association between MetS and osteocalcin. Clinical cross-sectional studies do not elucidate the potential role of sclerostin in the regulation of energy metabolism and direct experimental approach is necessary.